A Low‐Symmetry Dysprosium Metallocene Single‐Molecule Magnet with a High Anisotropy Barrier. Issue 37 (27th July 2016) - Pugh, Thomas; Chilton, Nicholas F.; Layfield, Richard A.
Abstract: The single‐molecule magnet (SMM) properties of the isocarbonyl‐ligated dysprosium metallocene [Cp*2 Dy{μ‐(OC)2 FeCp}]2 (1Dy ), which contains a rhombus‐shaped Dy2 Fe2 core, are described. Combining a strong axial [Cp*] − ligand field with a weak equatorial field consisting of the isocarbonyl ligands leads to an anisotropy barrier of 662 cm −1 in zero applied field. The dominant thermal relaxation pathways in1Dy involves at least the fourth‐excited Kramers doublet, thus demonstrating that prominent SMM behavior can be observed for dysprosium in low‐symmetry environments. Abstract : Kramers vs. Kramers : An isocarbonyl‐ligated dysprosium metallocene single‐molecule magnet (SMM) is designed and synthesized using a magnetostructural correlation. The SMM has a very large barrier of 662 cm −1, with magnetization reversal occurring via the fourth‐, fifth‐, and sixth‐excited Kramers doublets.